Harmonization of plant protection products dose expression and dose adjustment for high growing 3D crops: A review - Garcerá, Cruz; Doruchowski, Grzegorz; Chueca, Patricia (Elsevier, 2020)
This review outlines the background and current status of different dose expressions of plant protection products (PPP) applied in three-dimensional (3D) crops that are grown in orchards, groves, berry plantations, vineyards or greenhouses. It describes the course of dose expression harmonization process, and gives an overview of dose adjustment tools. In some EU countries there are used dose expressions that link the recommended amount of PPP with canopy height (CH), leaf wall area (LWA), tree row volume (TRV), or plant row distance (PRD). In the Mediterranean countries, a common way of PPP dosing recommendation is concentration of spray liquid. The advantages and disadvantages of each dose expression are discussed. Harmonization of dose expressions has for long been of great importance for the PPP authorization procedure, which in the EU is performed on a zonal basis. In the Central Zone it was agreed that the LWA model would be a common dose expression that must be used during efficacy trials in pome fruits, vines and high growing vegetables, and then in the subsequent zonal evaluation process. For the crops with wide canopies, such as citruses, olives or nuts, which are mainly grown in the Southern Zone, the TRV model might be a more appropriate dose expression to be agreed for a common use. However, any dose expression method should be corrected based on leaf area density. The crop-specific decision support tools, assisting growers to adjust effective PPP dose in specific circumstances, cover pome and stone fruits, citruses, olives, vines and greenhouse tomatoes